Internalization of Religious Moderation on Children at Raudhatul Athfal Samarinda - Musfiroh, Imroh Atul; Fauzan, Umar; Malihah, Noor (Southeast Asian Journal of Islamic Education, 2022)
This study aimed to analyze the process of internalizing the religious moderation values on children at an early age. The subjects of this research were principals, teachers, educational staff, parents and students at three Raudhatul Athfal schools in Samarinda. This research used qualitative design. Data collection was carried out for 2 months, from the beginning of February to the end of March 2022. Data obtained through observations, interviews, and documentation. The analysis of the data used the Miles and Huberman model that includes data condensation, data display, and conclusion and verification. The results showed that: 1) Planning of the internalization of religious moderation values on children ​​at Raudhotul Athfal Samarinda was through coordination between schools and stakeholders, identifying and determining school programs in accordance with the school curriculum, formulating materials regarding religious moderation values, formulating the planning of learning tools, 2) Implementation of internalization of the religious moderation values in learning was through the incorporation and strengthening of perspectives, mindsets and practices of religious moderation; curriculum development containing religious moderation through core competencies, building the values ​​of religious moderation through PAI and character education learning materials, 3) the results of the religious moderation value internalization were in the form of an understanding of the aswaja principles and moderate attitudes. It is expected that this research can give better insight related to the internalization of religious moderation values on children at an early age.